Long-term rates of knee arthroplasty in a cohort of 834 393 patients with a history of arthroscopic partial meniscectomy. (September 2019) - Abram, Simon G. F.; Judge, Andrew; Beard, David J.; Carr, Andrew J.; Price, Andrew J.
Abstract : Aims: The aim of this study was to determine the long-term risk of undergoing knee arthroplasty in a cohort of patients with meniscal tears who had undergone arthroscopic partial meniscectomy (APM). Patients and Methods: A retrospective national cohort of patients with a history of isolated APM was identified over a 20-year period. Patients with prior surgery to the same knee were excluded. The primary outcome was knee arthroplasty. Hazard ratios (HRs) were adjusted by patient age, sex, year of APM, Charlson comorbidity index, regional deprivation, rurality, and ethnicity. Risk of arthroplasty in the index knee was compared with the patient's contralateral knee (with vs without a history of APM). A total of 834 393 patients were included (mean age 50 years; 37% female). Results: Of those with at least 15 years of follow-up, 13.49% (16 256/120 493; 95% confidence interval (CI) 13.30 to 13.69) underwent subsequent arthroplasty within this time. In women, 22.07% (95% CI 21.64 to 22.51) underwent arthroplasty within 15 years compared with 9.91% of men (95% CI 9.71 to 10.12), corresponding to a risk ratio (RR) of 2.23 (95% CI 2.16 to 2.29). Relative to the general population, patients with a history of APM were over ten times more likely (RR 10.27; 95% CI 10.07 to 10.47) to undergo arthroplasty rising to almost 40 times more likely (RR 39.62; 95% CI 27.68 to 56.70) at a younger age (30 to 39 years). In patients with a history of APM in only one knee, the risk of arthroplasty in that knee was greatly elevated in comparison with the contralateral knee (no APM; HR 2.99; 95% CI 2.95 to 3.02). Conclusion: Patients developing a meniscal tear undergoing APM are at greater risk of knee arthroplasty than the general population. This risk is three-times greater in the patient's affected knee than in the contralateral knee. Women in the cohort were at double the risk of progressing to knee arthroplasty compared with men. These important new reference data will inform shared decision making and enhance approaches to treatment, prevention, and clinical surveillance. Cite this article: Bone Joint J 2019;101-B:1071–1080.